Some difficulties and challenges faced by project students in the Social Work Department, Faculty of Arts, Al-Sawan. (Comprehensive Journal of Science, 2026)
This study aimed to identify some of the difficulties and challenges faced by students working on projects in the Social Work Department at the Faculty of Arts, Al-Sawani. The researcher used the descriptive method and employed interviews as a data collection tool. The study yielded the following results: The most significant difficulty was related to choosing a research topic; the second most significant was academic and scientific difficulties; the third was related to resources and capabilities; the fourth was field-related difficulties; and the fifth was related to supervisors.
Keywords: difficulties, graduation project, Social Work Department.